2015
DOI: 10.1007/s00253-015-6579-0
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic streptococcal phage λSA2 and B30 endolysins kill streptococci in cow milk and in a mouse model of mastitis

Abstract: Bovine mastitis results in billion dollar losses annually in the United States alone. Streptococci are among the most relevant causative agents of this disease. Conventional antibiotic therapy is often unsuccessful and contributes to development of antibiotic resistance. Bacteriophage endolysins represent a new class of antimicrobials against these bacteria. In this work, we characterized the endolysins (lysins) of the streptococcal phages λSA2 and B30 and evaluated their potential as anti-mastitis agents. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 69 publications
0
70
0
Order By: Relevance
“…3). Such inconsistencies on a quantitative level between different methods used for analyzing synergy have been reported previously (37,38) and underline the necessity to characterize synergistic interactions in more than one assay format (39). Similarly, it is important to test PGHs and combinations thereof against multiple bacterial strains.…”
Section: Discussionmentioning
confidence: 99%
“…3). Such inconsistencies on a quantitative level between different methods used for analyzing synergy have been reported previously (37,38) and underline the necessity to characterize synergistic interactions in more than one assay format (39). Similarly, it is important to test PGHs and combinations thereof against multiple bacterial strains.…”
Section: Discussionmentioning
confidence: 99%
“…Synergism between lysins and antibiotics has been shown previously in the growth inhibition of facultative anaerobic bacteria (33,55). However, no synergism has been shown in the growth inhibition of strict anaerobic bacteria, possibly due to the challenge of maintaining the growth of anaerobic bacteria in minimal media.…”
Section: Discussionmentioning
confidence: 95%
“…These combined PGHs also showed high activity against the Staphylococcus epidermidis and Staphylococcus warneri strains tested in this study, which had shown high tolerance toward the individual PGHs (Table 2). Inconsistencies on a quantitative level between different methods used for analyzing synergy (e.g., the classical broth microdilution checkerboard assay and the 2-dimensional spot assay, which yielded ⌺FIC and ⌺FBC values for the Lyso:CHAP combination of 0.460 Ϯ 0.036 and 0.376 Ϯ 0.029, respectively) have been reported previously (37,38) and underline the necessity of characterizing synergistic interactions in more than one assay format (39). Similarly, it is important to test PGHs and combinations thereof against multiple bacterial strains.…”
Section: Screening For Endolysins With Activity In Milkmentioning
confidence: 99%